Ancestral Traditions of the Future: Where is traditional knowledge and practice preservation directed? - Semotiuk, Andrew J; Ezcurra, Exequiel; Colunga-GarcíaMarín, Patricia; Ahmad, Latif; Cuerrier, Alain (Ethnobotany Research and Applications, 2022)
Background: Traditional knowledge and practice prevalence is on an overall decline. In this study, we examine preservation strategies reported in the literature, follow-up measures, and categories of traditional knowledge and conservation practices that are being attempted by non-profit organizations. Methods: To answer these questions, we reviewed the literature for keywords related to TKP preservation and also searched databases of organizations with missions to preserve such knowledge. We found a range of traditional knowledge and practice preservation strategies that we categorized, and we provide a state of the current literature. The literature revealed anecdotal and qualitative follow-up measures with much emphasis on intellectual property rights. Results: The strongest argument we found came from anecdotal evidence showing the fundamental importance of experiential learning with elders on ancestral land for the purpose of passing traditions, ideas, and knowledge from one generation to the next. Further, non-profit organizations focused on policy and community education as predominant objectives in their mission statements. These results show the importance of follow-up measures (both quantitative and qualitative) on initiatives done in the field. Conclusions: TKP programs perform well when communities and local elders are consulted as they can foster culturally appropriate programs and provide a way to attract appreciation from the greater population. Overall, we recommend that both researchers and non-profit organizations assess these trends and caveats to help them form and direct their objectives to best conserve traditional knowledge and practices. Follow-up measurements, possibly based on museum-like surveys, would allow researchers to gain data for future initiatives. Keywords: Traditional knowledge and practices, ethnobiology, TKP, Indigenous Peoples’ Issues, Intellectual Property Rights, Preservation Strategies, ethno-education, protection of TKP, oral tradition, botanic gardens